The Function and Mechanism of Anti-Inflammatory Factor Metrnl Prevents the Progression of Inflammatory-Mediated Pathological Bone Osteolytic Diseases - Liu N; Dong J; Li L; Zhou D; Liu F (Dove Medical Press, 2024)
Nan Liu, Jinlei Dong, Lianxin Li, Dongsheng Zhou, Fanxiao Liu Department of Orthopedics, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, 250021, People's Republic of ChinaCorrespondence: Fanxiao Liu, Department of Orthopedics, Shandong Provincial Hospital affiliated to Shandong First Medical University, No. 324, Road Jing Wu Wei Qi, Jinan, Shandong, 250021, People's Republic of China, Tel +86-15069058755, Email woshi631@126.comAbstract: Metrnl, recently identified as an adipokine, is a secreted protein notably expressed in white adipose tissue, barrier tissues, and activated macrophages. This adipokine plays a pivotal role in counteracting obesity-induced insulin resistance. It enhances adipose tissue functionality by promoting adipocyte differentiation, activating metabolic pathways, and exerting anti-inflammatory effects. Extensive research has identified Metrnl as a key player in modulating inflammatory responses and as an integral regulator of muscle regeneration. These findings position Metrnl as a promising biomarker and potential therapeutic target in treating inflammation-associated pathologies. Despite this, the specific anti-inflammatory mechanisms of Metrnl in immune-mediated osteolysis and arthritis remain elusive, warranting further investigation. In this review, we will briefly elaborate on the role of Metrnl in anti-inflammation function in inflammation-related osteolysis, arthritis, and pathological bone resorption, which could facilitate Metrnl's clinical application as a novel therapeutic strategy to prevent bone loss. While the pathogenesis of elbow stiffness remains elusive, current literature suggests that Metrnl likely exerts a pivotal role in its development.Keywords: osteolysis, bone resorption, bone loss, Metrnl, arthritis, stiff elbow